Evaluating the Needs for English Material Among Economics Students - Achmad Kifi; Roudlotun Nurul Laili; Muhammad Nashir (Universitas Pahlawan Tuanku Tambusai, 2023)
In the context of globalization, proficiency in the English language is increasingly recognized as essential for students pursuing studies in economics. This study aimed to evaluate economics students' specific English language needs and provide recommendations for addressing these needs. This study involved a mixed methods approach, which utilizes both quantitative and qualitative research techniques. Questionnaires and interviews were employed as the data collection instruments. The findings underscore the importance of tailored English materials aligned with economics-specific terminology and concepts. The study suggests integrating economics key terms and vocabulary into the curriculum to support students in enhancing their English proficiency. Additionally, the research emphasizes the significance of collaborative efforts between economics faculty and English language instructors to develop effective teaching strategies and materials. The study concludes by highlighting the necessity of addressing the English language needs of economics students to prepare them for success in the global economic landscape.